OPPORTUNITIES AND CHALLENGES OF PROPERTY INVESTMENT IN INDONESIA - Vera Oktaviasari; Ayu Ayu (Review of International Economy and Finance, 2024)
Property investment is a profitable and promising business because the business always experiences an increase every year. Property investment is an investment in land, buildings or parts of buildings, or both, which are controlled by an entity to get rentals. Property investment has opportunities and challenges. The opportunity from property investment is that it can help national development because it can generate government revenues, both central and regional, and also help improve welfare, both directly (through job creation) and indirectly (through its contribution to national GDP). In addition, land and building prices continue to increase so that more and more buildings are emerging such as housing, apartments, shopping centers, or other property projects.